2020
DOI: 10.1002/oby.22841
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Body Weight, Hippocampal Volume, and Tissue Signal Intensity in 12‐ to 18‐Year‐Olds

Abstract: Objective: The hippocampus is a key structure in feeding behaviors and weight regulation. Obesity may lead to disruptions in hippocampal structure. In animals, obesity-related factors (e.g., high-fat/sugar foods) are associated with hippocampal insult (e.g., alterations in the blood brain barrier). In humans, individuals with obesity, relative to healthy weight, have smaller hippocampal volumes. Few studies have examined the association between body weight and the hippocampus during adolescence, a critical bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
1
5
1
Order By: Relevance
“…It may also be possible that excess body weight may differentially influence hippocampal structure in children and adolescents. In a recent study in older adolescents, BMI z-score was significantly associated with reduced hippocampal T2-weighted signal intensity, but not volume (Mestre et al, 2020). Together with the present results, these findings suggest BMI may influence hippocampal volume in childhood and tissue composition in late adolescence.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It may also be possible that excess body weight may differentially influence hippocampal structure in children and adolescents. In a recent study in older adolescents, BMI z-score was significantly associated with reduced hippocampal T2-weighted signal intensity, but not volume (Mestre et al, 2020). Together with the present results, these findings suggest BMI may influence hippocampal volume in childhood and tissue composition in late adolescence.…”
Section: Discussionsupporting
confidence: 82%
“…However, several cross-sectional studies that considered BMI across the weight spectrum, as opposed to testing for group differences using clinical obesity cut-offs, have not found a significant association (Masterson, Bobak, Rapuano, Shearrer, & Gilbert-Diamond, 2019;Mestre et al, 2020;Perlaki et al, 2018;Yau, Kang, Javier, & Convit, 2014). It is possible that these effects are subtle in nature and by employing shape analysis, we are able to probe the dosedependent effect of body mass on regional hippocampal structure that is typically obscured with whole-volumetric approaches.…”
Section: Discussionmentioning
confidence: 88%
“…Hippocampus is sensitive to diet and contributes to the regulation of food intake through the integration of hormonal (e.g., ghrelin, leptin) and cognitive (e.g., memory, learning, craving) signals (Stevenson & Francis, 2017 ). However, the relationship between hippocampal volume and weight status remains unclear as some studies have reported no association in children (Adise et al, 2021 ; Ou et al, 2016 ; Perlaki et al, 2018 ) or adolescents (Z. Mestre et al, 2020 ), while other studies show a mixed pattern of results. There is evidence that greater child weight status is associated with both lower left hippocampal volume (Bauer et al, 2015 ; Z. L. Mestre et al, 2017 ) and higher right hippocampal volume (Masterson, Bobak et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between hippocampal volume and weight status remains unclear as some studies have reported no association in children (Adise et al, 2021;Ou et al, 2016;Perlaki et al, 2018) or adolescents (Z. Mestre et al, 2020), while other studies show a mixed pattern of results. There is evidence that greater child weight status is associated with both lower left hippocampal volume (Bauer et al, 2015;Z.…”
mentioning
confidence: 99%
“…Both adults and children with obesity show smaller hippocampal volumes, relative to those with healthy weight [ 137 , 139 , 140 ]. A large study among adolescents across the weight spectrum showed that BMI was not associated with hippocampal volume but was associated with measures of tissue integrity [ 141 ].…”
Section: Neural Understandings Of Fcr In Humansmentioning
confidence: 99%